Политология: учебник для вузов / А. С. Панарин; Моск. гос. ун-т им. М. В. Ломоносова - Панарин Александр Сергеевич (Проспект, 2000)
Экземпляры: (20171127) / Инвентарный номер: 1937 / Цена: / Сис.шифр: 66.0я7 / Авт.знак: П 16 / ББК: 66.0я7